Climate Change and Migration: A Dynamic Model - Charles F. Mason (Center for Economic Studies and ifo Institute (CESifo), 2016)
In this paper I explore a model where citizens of a country vulnerable to damages from climate change may migrate to a second country, from which a steady stream of greenhouse gases occur. If this migration imposes costs on the emitting country, then migration induces a sort of pseudo carbon tax.via political economic forces. This pseudo tax creates an incentive for the country receiving the flow of immigrants to lower its emissions, offering an offset to the costs incurred as a result of climate change. I show that the long run carbon stock, and the entire time path of production (and hence emissions), is smaller in the presence of migration. I discuss various comparative dynamics, for both the path of production and the long run atmospheric carbon stock.
Keywords: Q54; 330; transboundary pollution; migration; optimal control